The SGLT-2 Inhibitor Dapagliflozin Has a Therapeutic Effect on Atherosclerosis in Diabetic ApoE−/− Mice - Weiling Leng; Xinshou Ouyang; Xiaotian Lei; Mingxia Wu; Liu Chen; Qinan Wu; Wuquan Deng; Ziwen Liang (Mediators of Inflammation)
Background. Our study aimed to observe the effect of sodium glucose cotransporter-2 (SGLT2) inhibitor dapagliflozin on diabetic atherosclerosis and investigate the subsequent mechanism. Methods. Aortic atherosclerosis was induced in streptozotocin induced diabetic ApoE−/− mice by feeding with high-fat diet, and dapagliflozin was administrated intragastrically for 12 weeks as treatment. Effects of dapagliflozin on indices of glucose and fat metabolism, IL-1β, IL-18, NLRP3 protein levels, and the reactive oxygen species (ROS) were measured. The atherosclerosis was evaluated by oil red O and hematoxylin-eosin staining. The effects of dapagliflozin on the IL-1β production in culturing primary macrophages of wild type and NLRP3−/− knockout mice were investigated for mechanism analyses. Results. Dapagliflozin treatment showed favorable effects on glucose and fat metabolism, partially reversed the formation of atherosclerosis, inhibited macrophage infiltration, and enhanced the stability of lesion. Also, reduced production of IL-1β, IL-18, NLRP3 protein, and mitochondrial ROS in the aortic tissues was detected with dapagliflozin treatment. In vitro, NLRP3 inflammasome was activated by hyperglucose and hyperlipid through ROS pathway. Conclusions. Dapagliflozin may be of therapeutic potential for diabetic atherosclerosis induced by high-fat diet, and these benefits may depend on the inhibitory effect on the secretion of IL-1β by macrophages via the ROS-NLRP3-caspase-1 pathway.